Securities Transaction Tax Reduction and Stock-Futures Arbitrage in India: A Case Study - Slivka, Ronald T.; Aggarwal, Pankaj; Sisodia, Raghvendra (Indian Journal of Finance, 2012)
UK Sinha, Chairman of the Securities Exchange Board of India (SEBI) announced in November, 2011 that SEBI had engaged the Ministry of Finance in a discussion, that would hopefully lead to a reduction of India’s Securities Transaction Tax (STT) - a discussion that would hopefully produce benefits for India’s capital markets (CNBC, 2011). The matter of reducing or eliminating the STT was under study by the Ministry of Finance, Government of India and came before the Indian Parliament in February 2012. Removal of this tax has been a long-term objective of brokers, stock exchanges and investors, who compare the exceptionally high total transaction cost of fees and taxes in India with lower total costs in other countries. In this study, both intraday and inter-day data on a representative selection of single stocks and their associated futures contracts was used to explore the effects of reduction or elimination of the STT when single stocks are arbitraged against their related futures contracts. For this purpose, data was chosen spanning selected days in June through December 2011 for eight liquid single stocks. Since the profit from a potential arbitrage can be calculated in advance of entering a trade, the number of profitable single stock arbitrage trades available on a specific day can be calculated after accounting for STT cost ranging from zero to 100% of its current statutory level. The result of this careful analysis suggested that a decrease in the STT of at least 75% is necessary to achieve meaningfully increased levels of arbitrage normally found in most successful global futures markets. Such a decrease in the STT is also likely to result in the maximum transaction revenue collected by the government.